ANALISIS FAKTOR YANG MEMPENGARUHI KEMISKINAN PADA SEKTOR PERTANIAN DI INDONESIA BAGIAN BARAT - Safira Maulidina; Vadilla Mutia Zahara; Hady Sutjipto (National Conference on Applied Business, Education, & Technology (NCABET), 2022)
In developing countries, poverty and the agricultural sector are closely linked. This study aims to analyze the agricultural sector GRDP, the exchange rate of farmers, employment, education and unemployment in the agricultural sector influencing poverty in western Indonesia. The panel data model is used with fixed effect model estimates for data from 11 provinces from 2016 to 2020. The results show that Agricultural Sector GRDP and Unemployment have a significant positive effect on Poverty. The results also show that the exchange rate and the education of farmers have a significant negative effect on poverty. However, the results of the variable Work in the Agricultural Sector do not have a significant effect on Poverty. Another implication of this situation is that the increase in GRDP in the agricultural sector and unemployment are factors causing the increase in poverty in western Indonesia. Meanwhile, rising farmers' exchange rates, education and unemployment variables can help reduce poverty in western Indonesia. Therefore, this research will be useful for policymakers, both central and local governments, to always pay attention to the variables that can affect the incidence of poverty in western Indonesia